Lenticellaria and Hillerella, new kraussinoid genera (Kraussinoidea, Brachiopoda) from Indo-Pacific and Red Sea waters: evolution in the subfamily Megerliinae - Simon, Eric G; Logan, Alan; Zuschin, Martin; Mainguy, Jerome; Mottequin, Bernard (Zootaxa, 2016)
Two new kraussinid brachiopod genera, namely Lenticellaria gen. nov. and Hillerella gen. nov. are described from Pacific waters in the sub-equatorial zone in the Indonesian Archipelago, from Indian Ocean waters in Madagascar and from Red Sea waters in Egypt (Gulf of Aqaba) and Sudan. This fills the equatorial gap in the distribution of the superfamily Kraussinoidea, known from higher latitudes in both hemispheres. The micromorphic new material described is an excellent example of homeomorphy in brachiopods. It also provides new information on the distribution of the genus Megerlia sensu stricto and illustrates subtle variations in the evolutionary process of the reduced brachidium in Kraussinoidea.